2009
DOI: 10.1007/s00018-009-0206-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac sulfide suppresses 5-lipoxygenase at clinically relevant concentrations

Abstract: Sulindac is a non-selective inhibitor of cyclooxygenases (COX) used to treat inflammation and pain. Additionally, non-COX targets may account for the drug's chemo-preventive efficacy against colorectal cancer and reduced gastrointestinal toxicity. Here, we demonstrate that the pharmacologically active metabolite of sulindac, sulindac sulfide (SSi), targets 5-lipoxygenase (5-LO), the key enzyme in the biosynthesis of proinflammatory leukotrienes (LTs). SSi inhibited 5-LO in ionophore A23187- and LPS/fMLP-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The amount of LTB 4 and Ssi also exhibited different potencies in male and female blood. In contrast to other typical direct 5-LO inhibitors, licofelone and Ssi blocked 5-LO nuclear translocation, were more potent in intact cells than for isolated 5-LO, and, at least for licofelone, FLAP has been identified as a pharmacologically relevant target (32,33). Together, the agonist-induced assembly of the tight LTbiosynthetic 5-LO/FLAP complex occurs primarily in female cells, but hardly in male cells (impeded by androgens), which explains why LT synthesis inhibitors that act by preventing the 5-LO/FLAP interaction are more effective in females.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The amount of LTB 4 and Ssi also exhibited different potencies in male and female blood. In contrast to other typical direct 5-LO inhibitors, licofelone and Ssi blocked 5-LO nuclear translocation, were more potent in intact cells than for isolated 5-LO, and, at least for licofelone, FLAP has been identified as a pharmacologically relevant target (32,33). Together, the agonist-induced assembly of the tight LTbiosynthetic 5-LO/FLAP complex occurs primarily in female cells, but hardly in male cells (impeded by androgens), which explains why LT synthesis inhibitors that act by preventing the 5-LO/FLAP interaction are more effective in females.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, the FLAP inhibitor from the quinoline series BAY-X 1005 (31), also known as DG-031 or veliflapon, was significantly more potent in female than in male blood ( Figure 3B), and a similar tendency was observed for the FLAP inhibitor MK591, an indole-quinoline hybrid (Supplemental Table 2). Finally, licofelone (a biphenyl pyrrolizine) and sulindac sulfide (Ssi, an indene derivative), which are classified as novel-type 5-LO inhibitors that preferentially interfere with cellular activation of 5-LO by blocking 5-LO translocation to the nuclear membrane where FLAP resides (32,33), were effective only in female blood ( Figure 3B and Supplemental Table 1). Together, FLAP inhibitors and distinct novel-type 5-LO inhibitors that block 5-LO nuclear translocation are more efficient in female blood, whereas no sex differences were observed for a cPLA 2 inhibitor and various types of direct 5-LO inhibitors.…”
Section: Sex Differences In the Effects Of Lt Biosynthesis Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 5-LO-inhibitory concentrations were similar to those for suppression of Wnt signaling and the aberrant self-renewal of LSCs (16,17).…”
Section: Introductionmentioning
confidence: 68%
“…6,7,[13][14][15][16][26][27][28][29]. It has recently been shown that sulindac sulfide (active metabolite of sulindac) is able to inhibit 5-LO at clinically relevant concentrations (17). Therefore, we investigated whether other NSAIDs such as indomethacin are able to inhibit 5-LO.…”
Section: -Lo Is Inhibited By Nsaids and Is Expressed In Normal And Mmentioning
confidence: 99%